Participation in Courts and Tribunals Concepts, Realities and Aspirations - Jacobson, Jessica; Cooper, Penny (Policy Press, 2020)
Available Open Access under CC-BY-NC licence. Barriers to participation in the court system is a recurring and important problem within the criminal justice system. This significant study reveals how participation is supported in the courts and tribunals of England and Wales. Including reflections on changes to the justice system as a result of the COVID-19 pandemic, it also details the socio-structural, environmental, procedural, cultural and personal factors which constrain participation.